Association of Complement-Related Proteins in Subjects With and Without Second Trimester Gestational Diabetes - Ramanjaneya, Manjunath; Butler, Alexandra E.; Alkasem, Meis; Bashir, Mohammed; Jerobin, Jayakumar; Godwin, Angela; Moin, Abu Saleh Md; Ahmed, Lina; Elrayess, Mohamed A.; Hunt, Steven C.; Atkin, Stephen L.; Abou-Samra, Abdul-Badi (Frontiers in Endocrinology, 2021)
Introduction. Gestational Diabetes Mellitus (GDM) development is related to underlying metabolic syndrome that is associated with elevated complement C3 and C4. Elevated C3 levels have been associated with preeclampsia and the development of macrosomia. Methods. This prospective case-control study included 34 pregnant women with GDM and 16 non-diabetic (ND) women in their second trimester. Complement-related proteins were measured and correlated with demographic, biochemical, and pregnancy outcome data. Results. GDM women were older with a higher BMI (p<0.001); complement C3, C3b/iC3b, C4 and Factor-H were significantly elevated (p<0.001, p=0.01, p=0.04, p=0.01, respectively). Partial correlation showed significant correlation between C4 with serum alanine aminotransferase (ALT) (p<0.05) and 2nd term diastolic blood pressure (p<0.05); Factor-H and C-reactive protein (CRP; p<0.05). Pearson bivariate analysis revealed significant correlations between C3, C4 and Factor-H and CRP; p<0.05; C3 and gestational age at delivery (GA; p<0.05); C4 and ALT and second-trimester systolic blood pressure (STBP) (p=0.008 and p<0.05, respectively); Factor-H and glycated hemoglobin (HbA1c) (p<0.05). Regression analysis showed that the elevation of C3 could be accounted for by age, BMI, GA and CRP, with CRP being the most important predictor (p=0.02). C4 elevation could be accounted for by ALT, CRP and STBP. CRP predicted Factor-H elevation. Conclusion. The increased C3, C4 and Factor-H during the second trimester of pregnancy in GDM are not independently associated with GDM; inflammation and high BMI may be responsible for their elevation. The elevation of second trimester C3 in GDM is associated with earlier delivery and further work is needed to determine if this is predictive.